﻿Adapting To Climate Change In Africa - Denton, Fatima; O'Neill, Mary; Stone, John M.R. (World Bank, 2012)
Discusses the Climate Change Adaptation in Africa program, which aims to establish a self-sustained African body of expertise on adaptation through capacity development and strengthening institutions.